2012
DOI: 10.1108/09578231211249871
|View full text |Cite
|
Sign up to set email alerts
|

Bridging accountability obligations, professional values and (perceived) student needs with integrity

Abstract: PurposeThe purpose of this paper is to explore the tensions between external accountability obligations, educator's professional values, and student needs. Strategic, cognitive, and moral dimensions of this tension are captured with the central category of integrity.Design/methodology/approachThis is a mixed methods study that compares five exceptionally high performing middle schools with four exceptionally low performing middle schools in the state of California (USA), controlling for demographics, school co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
50
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 49 publications
10
50
0
9
Order By: Relevance
“…Studies have also demonstrated how urban principals used and essentially manipulated external accountabilities (such as test scores) as means to compel their school communities towards improvement (Knapp and Feldman 2012). Other scholars have emphasised how internal accountabilities such as personal integrity and conscience remain central motivators of principals (Gonzalez and Firestone 2013;Mintrop 2012). Terosky (2014) profiled how New York City principals asserted individual agency in order to follow a 'learning imperative' (1) rather than merely a managerial imperative, thus overcoming what other scholars have described as urban school principals' sense of 'limited control' amidst 'relentless accountability' (West, Peck, and Reitzug 2010, 238).…”
Section: Related Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…Studies have also demonstrated how urban principals used and essentially manipulated external accountabilities (such as test scores) as means to compel their school communities towards improvement (Knapp and Feldman 2012). Other scholars have emphasised how internal accountabilities such as personal integrity and conscience remain central motivators of principals (Gonzalez and Firestone 2013;Mintrop 2012). Terosky (2014) profiled how New York City principals asserted individual agency in order to follow a 'learning imperative' (1) rather than merely a managerial imperative, thus overcoming what other scholars have described as urban school principals' sense of 'limited control' amidst 'relentless accountability' (West, Peck, and Reitzug 2010, 238).…”
Section: Related Literaturementioning
confidence: 96%
“…In doing so, we build on previous research that has examined the work lives and attitudes of principals (Leithwood et al 2004;Mintrop 2012;Shipps 2012;Spillane and Hunt 2010). Specifically, we investigate how principals responded to two different superintendents (chief school system leaders) in a large urban school district in the Southeastern United States.…”
mentioning
confidence: 98%
“…First, as discussed in the introduction, Finnigan (2010), Mintrop (2012), Gawlik (2015), and others have demonstrated that accountability policies and frameworks influence the behaviors and performance of schools, school employees, and accountability agents. In other words, there is reason to suspect that the ways in which administrators view accountability frames their relationship with DPI and the public in ways that affect their performance.…”
Section: Who Are Mpcp Administrators and Why Do Their Perceptions Matmentioning
confidence: 98%
“…Biesta (2004), for example, provided a theoretical understanding of the importance of accountability by describing the ways in which accountability frameworks define the relationships between school employees, schools, government agencies, and the public at large. Similarly, Rutledge (2010), Finnigan (2010), and Mintrop (2012) demonstrated how high-stakes accountability policies impact the behavior of actors within schools. Gawlik (2015) looked specifically at the case of charter schools and concluded that school actors' perceptions of accountability influence the behaviors and policy preference of charter-school leaders.…”
mentioning
confidence: 96%
“…Schools with low-SES and higher levels of enrolled minority students reported more focus on local, building-level goal-setting. The literature has shown how local-level leaders often deflect the influence and control of top-down policies, choosing to focus more on local school and community concerns and student data (Alsbury & Whitaker, 2007;Malen, 2003;Miller, 2010;Mintrop, 2012;Sherman, 2008).…”
Section: Discussionmentioning
confidence: 99%